COMPARISON OF REALTIME-PCR TO ELISA FOR THE DETECTION OF HUMAN CYTOMEGALOVIRUS INFECTION IN THAI BINH PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: This paper presents the results of comparison of Real-time Polymerase ChainReaction (PCR) to Enzyme-linked immunosorbent assay (Elisa) for the detection of humancytomegalovirus infection in paediatric patients and determine the correlation betweenclinical features to Elisa and Realtime PCR.Subjects and methods: This study was carried out to detect human cytomegalovirus IgGand IgM antibodies using Elisa in under 6 years old paediatric patients in ThaiBinh paediatrichospital and to improve the diagnosis of HCMV through the introduction of PCR testing.There were 132 patients in the study.Results: The results revealed that HCMV IgG was present in patients’ blood 124/132(93.9%), while 90/132 (68.2%) had IgM, 78/132 (59.1%) had IgG and IgM. HCMV DNAviral loads were detected in patients had IgG 74.2% and 94.4% in patients had IgM usingReal-time PCR. However, the rate of detection HCMV DNA in negative samples are 12.5%in IgG {-} patients and 26.2% in IgM {-} patients.Conclusion: This result is the basis for the right treatments in patients to avoid unfortunatecomplications.
Keywords: CMV, IgG, IgM, paediatric patients, new-born.